1993
DOI: 10.1002/cm.970240202
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal sheets of mammalian eggs and embryos: A lattice‐like network of intermediate filaments

Abstract: Mammalian eggs and embryos possess a major cytoskeletal network composed of large planar "sheets" distributed throughout the cytoplasm. Cytoskeletal sheets are found neither in mammalian somatic cells nor in eggs or embryos of non-mammals. In this study, we have investigated the structural composition of the sheets in eggs and embryos of the golden Syrian hamster by (1) analysis of replicas from quick-frozen, deep-etched specimens, (2) analysis of thick, resin-embedded specimens using an intermediate voltage e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
1
34
2
Order By: Relevance
“…This is a particular problem when imaging events that occur over periods of time ranging from hours to days, such as embryonic development. For this reason, much of our current understanding of subcellular morphological changes during mammalian embryonic development is based on images of fixed or static specimens at different developmental stages [2][3][4][5][6] . Thus, it can be difficult to interpret dynamic processes accurately, because the continuity of events must be inferred.…”
mentioning
confidence: 99%
“…This is a particular problem when imaging events that occur over periods of time ranging from hours to days, such as embryonic development. For this reason, much of our current understanding of subcellular morphological changes during mammalian embryonic development is based on images of fixed or static specimens at different developmental stages [2][3][4][5][6] . Thus, it can be difficult to interpret dynamic processes accurately, because the continuity of events must be inferred.…”
mentioning
confidence: 99%
“…CPLs are highly abundant in the oocytes and have long been predicted to function as a storage form for the maternal contribution of ribosomes to the early embryo [29]. Additional work confirmed their involvement in ribosomal storage in oocytes [28] and showed that PADI6, NLRP5/MATER [32], and FLOPED/OOEP co-localize at the CPLs and are required for their formation.…”
Section: Potential Involvement Of the Scmc In Regulation Of Translationmentioning
confidence: 87%
“…1 Schematic representation of the hypothesized structure of the SCMC and localization within the MII oocyte Interestingly, PADI6 was seen to localize to [26] and be essential for the formation of the oocyte cytoplasmic lattices (CPLs), a fibrillar matrix composed of a proteinaceous component and RNA [27,28]. The CLPs contain five to seven parallel fibers with repeating units of about 20 nm [29]. The bundled fibers are first observed at early stages of oocyte growth (30-40 μm) [30] and persist in the early embryo until the blastocyst stage [31].…”
Section: Potential Involvement Of the Scmc In Regulation Of Translationmentioning
confidence: 99%
“…Trim the block face to produce a square. Blocks are sectioned on an ultramicrotome with a knife angle adjusted to10° (Capco et al, 1993). 200 nm sections are collected on formvar-coated, carbon-stabilized grids precoated with poly-L-lysine and subsequently dried overnight in a vacuum desiccator.…”
Section: Procedures For Embedment-free Electron Microscopy For Use Witmentioning
confidence: 99%